DOI: 10.33915/etd.4021
|View full text |Cite
|
Sign up to set email alerts
|

Soil Health Assessment in Reclaimed Mine Soils

Abstract: my committee members, not only for their time, but for their wisdom and much needed input throughout the process of my research. I would also like to thank Dr. James Thompson for always pushing me to be my best, and for truly guiding me toward my love of soil science and pedology. Dr. John Grove (University of Kentucky) and Dr. Domingo Mata-Padrino also supported my research by providing expertise and help whenever they saw the opportunity. I am truly blessed to have had such a wonderful support system within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Exotic grasses and forbs with native prairie species mixture proved to be versatile in filling a variety of niches and improved the ecosystem function of abandoned coal mine areas of Ohio thus providing a feasible reclamation approach (Swab et al, 2017). Stutler (2019) reported that coal mine sites containing less variation between legumes, forbs and grass species showed 44% more biomass yield and N pool accretion of 4.14 Mg ha −1 compared with sites with more forbs and more grasses. The work of Harantova et al (2017) reported total N accumulation of 2600–4000 mg kg −1 in 0–54 years of coal mine reclamation, respectively, when more than 60% of understory vegetation cover was dominated by grass ( Calamagrostis epigejos) , legumes ( Melilotus albus and Trifolium medium) and forbs ( Leontodon hispidus) along with common grassland species.…”
Section: Reclamation Approachesmentioning
confidence: 99%
“…Exotic grasses and forbs with native prairie species mixture proved to be versatile in filling a variety of niches and improved the ecosystem function of abandoned coal mine areas of Ohio thus providing a feasible reclamation approach (Swab et al, 2017). Stutler (2019) reported that coal mine sites containing less variation between legumes, forbs and grass species showed 44% more biomass yield and N pool accretion of 4.14 Mg ha −1 compared with sites with more forbs and more grasses. The work of Harantova et al (2017) reported total N accumulation of 2600–4000 mg kg −1 in 0–54 years of coal mine reclamation, respectively, when more than 60% of understory vegetation cover was dominated by grass ( Calamagrostis epigejos) , legumes ( Melilotus albus and Trifolium medium) and forbs ( Leontodon hispidus) along with common grassland species.…”
Section: Reclamation Approachesmentioning
confidence: 99%
“…The carbon dioxide levels were influenced by the soil texture, with the clay-textured soil showing the highest value of 31.16 mg CO2 100 g−1 dry soil 24 h−1, while the sandy loam soil had the lowest value of 15.97 mg CO2 100 g−1 dry soil 24 h−1. Both values fall within the specified range of 14.29-28.57 units according to the report conducted a study which concluded that clayey soil has a greater degree of biological activity in comparison to other soil types [24,25]. The findings indicate that there is a positive correlation between the clay content of the soil and soil respiration.…”
Section: Methodsmentioning
confidence: 64%